The gravity model and the classification of countries - Menkes, Jerzy; Czarny, Elżbieta; Śledziewska, Katarzyna (Uniwersytet Ekonomiczny we Wrocławiu, 2010)
We discuss the gravity equation based on Helpman’s theorem (1987) using the approach of Debaere (2005). Unlike Debaere, we do not constrain our analysis to the split into OECD and non-OECD, but we propose an alternative division. We argue that the division of countries into OECD and non-OECD is not an appropriate representation of – respectively – developed and less developed countries. Instead, we propose the division of non-OECD countries into two groups: the first one consisting of non-OECD countries fulfilling membership criteria and the second one, not fulfilling these criteria. In our setting, the less developed countries are collected only in the last group, whereas OECD and non-OECD countries fulfilling membership criteria are the developed ones. We analyze trade between pairs of countries and aggregate the results to illustrate trade between the three above mentioned groups of countries in the period of 28 years (1977-2005). We show that the Helpman’s theorem designed to explain trade among developed countries still does not find support among less developed ones unless the last group is properly extracted.
Argumenta Oeconomica, 2010, Nr 2 (25), s. 79-94
Keywords: gravity model; international trade